Synthetic high-density lipoprotein (sHDL): a bioinspired nanotherapeutics for managing periapical bone inflammation - Renan Dal-Fabbro; Minzhi Yu; Ling Mei; Hajime Sasaki; Anna Schwendeman; Marco C. Bottino (International Journal of Oral Science, 2024)
Abstract Apical periodontitis (AP) is a dental-driven condition caused by pathogens and their toxins infecting the inner portion of the tooth (i.e., dental pulp tissue), resulting in inflammation and apical bone resorption affecting 50% of the worldwide population, with more than 15 million root canals performed annually in the United States. Current treatment involves cleaning and decontaminating the infected tissue with chemo-mechanical approaches and materials introduced years ago, such as calcium hydroxide, zinc oxide–eugenol, or even formalin products. Here, we present, for the first time, a nanotherapeutics based on using synthetic high-density lipoprotein (sHDL) as an innovative and safe strategy to manage dental bone inflammation. sHDL application in concentrations ranging from 25 µg to 100 µg/mL decreases nuclear factor Kappa B (NF-κB) activation promoted by an inflammatory stimulus (lipopolysaccharide, LPS). Moreover, sHDL at 500 µg/mL concentration markedly decreases in vitro osteoclastogenesis (P < 0.001), and inhibits IL-1α (P = 0.027), TNF-α (P = 0.004), and IL-6 (P < 0.001) production in an inflammatory state. Notably, sHDL strongly dampens the Toll-Like Receptor signaling pathway facing LPS stimulation, mainly by downregulating at least 3-fold the pro-inflammatory genes, such as Il1b, Il1a, Il6, Ptgs2, and Tnf. In vivo, the lipoprotein nanoparticle applied after NaOCl reduced bone resorption volume to (1.3 ± 0.05) mm3 and attenuated the inflammatory reaction after treatment to (1 090 ± 184) cells compared to non-treated animals that had (2.9 ± 0.6) mm3 (P = 0.012 3) and (2 443 ± 931) cells (P = 0.004), thus highlighting its promising clinical potential as an alternative therapeutic for managing dental bone inflammation.